Tumor-released autophagosomes induce IL-10-producing B cells with suppressive activity on T lymphocytes via TLR2-MyD88-NF-κB signal pathway. (2nd July 2016) - Zhou, Meng; Wen, Zhifa; Cheng, Feng; Ma, Jie; Li, Weixia; Ren, Hongyan; Sheng, Yemeng; Dong, Huixia; Lu, Liwei; Hu, Hong-Ming; Wang, Li-Xin
ABSTRACT: Recent studies have shown that tumor cells can release autophagosomes, which transport a broad array of biologically active molecules with potential modulatory effects on immune cell functions. In this study, we aimed to investigate the role of tumor cells-released autophagosomes (i.e. TRAP) in regulating B cell differentiation and function. TRAPs from murine tumor cell lines were found to induce splenic B cells to differentiate into IL-10-producing regulatory B cells (Bregs) with a distinct phenotype of CD1d + CD5 +, which could potently inhibit CD8 + and CD4 + T cell responses in IL-10-depedent manner both in vitro and in vivo . Notably, adoptive transfer of TRAP-induced Bregs abrogated the immune response and antitumor effect induced by OVA-loaded DC vaccinations in E.G7-OVA-bearing mouse model. Mechanistic studies revealed that membrane-bound high-mobility group B1 (HMGB1) on the intact TRAPs was crucial for inducing Breg differentiation via the activation of TLR2-MyD88-NF-κB signal pathway in B cells. Moreover, TRAPs enriched from malignant effusions of cancer patients could induce human B cells to differentiate into IL-10-producing B cells with immunoregulatory functions, the frequency of which were positively correlated with the HMGB1 levels on TRAPs. Together, our findings have demonstrated that TRAPs promote the generation of IL-10 + Bregs, which may contribute to the suppression of antitumor immunity.